Birth, evolution, and transmission of satellite-free mammalian centromeric domains - Nergadze, Solomon G.; Piras, Francesca M.; Gamba, Riccardo; Corbo, Marco; Cerutti, Federico; McCarter, Joseph G.W.; Cappelletti, Eleonora; Gozzo, Francesco; Harman, Rebecca M.; Antczak, Douglas F.; Miller, Donald; Scharfe, Maren; et al.

(untitled) (Genome Research, 2018)
Mammalian centromeres are associated with highly repetitive DNA (satellite DNA), which has so far hindered molecular analysis of this chromatin domain. Centromeres are epigenetically specified, and binding of the CENPA protein is their main determinant. In previous work, we described the first example of a natural satellite-free centromere on Equus caballus Chromosome 11. Here, we investigated the satellite-free centromeres of Equus asinus by using ChIP-seq with anti-CENPA antibodies. We identified an extraordinarily high number of centromeres lacking satellite DNA (16 of 31). All of them lay in LINE- and AT-rich regions. A subset of these centromeres is associated with DNA amplification. The location of CENPA binding domains can vary in different individuals, giving rise to epialleles. The analysis of epiallele transmission in hybrids (three mules and one hinny) showed that centromeric domains are inherited as Mendelian traits, but their position can slide in one generation. Conversely, centromere location is stable during mitotic propagation of cultured cells. Our results demonstrate that the presence of more than half of centromeres void of satellite DNA is compatible with genome stability and species survival. The presence of amplified DNA at some centromeres suggests that these arrays may represent an intermediate stage toward satellite DNA formation during evolution. The fact that CENPA binding domains can move within relatively restricted regions (a few hundred kilobases) suggests that the centromeric function is physically limited by epigenetic boundaries.